SINgapore GERiatric intervention study to reduce physical frailty and cognitive decline (SINGER)–pilot: A feasibility study. Issue 1 (15th March 2021) - Chew, Kimberly Ann; Xu, Xin; Siongco, Paula; Villaraza, Steven; Phua, April Ka Sin; Wong, Zi Xuen; Chung, Chooi Yu; Tang, Ning; Chew, Effie; Henry, Christiani Jeyakumar; Koo, Edward; Chen, Christopher
Abstract: Introduction: The SINGER pilot randomized controlled trial aims to examine the feasibility and acceptability of the Finnish Geriatric Intervention Study (FINGER) multi‐domain lifestyle interventions compared to Singaporean adaptations. Methods: Seventy elderly participants were recruited and randomized into FINGER (n = 36) or SINGER (n = 34) interventions; involving physical exercise, cognitive training, diet, and vascular risk factors management, for 6 months. Results: Both intervention groups were equally feasible and acceptable with participants completing at least 80% of the interventions. Body strength improved in both groups ( Pupper body = .04, P lower body = .06, P core = .05). More participants in the SINGER group attained good blood pressure control at month‐6 compared to FINGER (41% vs 19%; P = .06). Discussion: This study is the first to compare the feasibility of multi‐domain interventions adapted to local culture with the FINGER interventions. The findings will be utilized for a larger study to provide evidence for the efficacy of multi‐domain lifestyle interventions in preventing cognitive decline.